Adaptation of Business Actors to New Policy Transformations - Deranika Ratna Kristiana; Atika Jauharia Hatta Hambali (E-Jurnal Akuntansi, 2025)
This study examines the adaptation of Micro, Small, and Medium Enterprises (MSMEs) to the new policy transformation in Indonesia's taxation system. With significant contributions to Gross Domestic Product (GDP) and employment, MSMEs are the core of the national economy, but they face challenges in terms of tax compliance. Through a quantitative approach and descriptive and explanatory methods, this study analyzes the effect of new policies, the quality of the DJP Online system, tax officer responses, and tax socialization on MSME tax compliance. Data were taken from 66 business actors in the Special Region of Yogyakarta and Central Java. The results of the study indicate that the quality of the DJP Online system and tax socialization significantly affect MSME tax compliance. In contrast, new policies and responses from tax officers do not show a significant impact. These findings reflect the need for more effective socialization and better system quality to improve tax compliance among MSMEs. This study is expected to provide useful recommendations for the government in formulating adaptive, inclusive, and future-oriented policy strategies for improving tax compliance in the digital era.